Hydrogen peroxide scavenger, catalase, alleviates ion transport dysfunction in murine colitis. (November 2016) - Barrett, Kim E; McCole, Declan F
Summary: Reactive oxygen species (ROS) such as hydrogen peroxide (H2 O2 ) contribute to epithelial damage and ion transport dysfunction (key events in inflammatory diarrhoea) in inflammatory bowel disease (IBD). The aim of this study was to identify if H2 O2 mediates suppression of colonic ion transport function in the murine dextran sulfate sodium (DSS) colitis model by using the H2 O2 degrading enzyme, catalase. Colitis was induced by administering DSS (4%) in drinking water for 5 days followed by 3 days on normal H2 O. Mice were administered either pegylated catalase or saline at day −1, 0 and +1 of DSS treatment. Ion transport responses to the Ca 2+ ‐dependent agonist, carbachol (CCh), or the cAMP‐dependent agonist, forskolin, were measured across distal colonic mucosa mounted in Ussing chambers. Parameters of DSS‐induced inflammation (loss in body weight, decreased colon length, altered stool consistency), were only partially alleviated by catalase while histology was only minimally improved. However, catalase significantly reversed the DSS‐induced reduction in baseline ion transport as well as colonic Isc responses to CCh. However, ion transport responses to forskolin were not significantly restored. Catalase also reduced activation of ERK MAP kinase in the setting of colitis, and increased expression of the Na + ‐K + ‐2Cl − cotransporter, NKCC1, consistent with restoration of ion transport function. Ex vivo treatment of inflamed colonic mucosae with catalase also partially restored ion transport function. Therefore, catalase partially prevents, and rescues, the loss of ion transport properties in DSS colitis even in the setting of unresolved tissue inflammation. These findings indicate a prominent role for ROS in ion transport dysfunction in colitis and may suggest novel strategies for the treatment of inflammatory diarrhoea.